TINJAUAN KOORDINASI ANTARA POLITEKNIK PENERBANGAN INDONESIA CURUG DAN BUDIARTO AIR TRAFFIC SERVICES TERHADAP KESELAMATAN PENERBANGAN DI PERUM LPPNPI CABANG PEMBANTU CURUG - Hasby Assidiqi Munadhir; Wasito Utomo; Arnaz Olieve (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
There are two kinds of communication systems in air traffic control named ground-to-ground communication system and air-to-ground flight communication system. The ground-to-ground communication system is used by ATC (Air Traffic Controller) officers with pilots when moving on the ground and communication between the airports. For safety purposes, any aircraft movements in the Movement Area are carried out by the pilot under the ATC (Air Traffic Controller) order from the control tower. Therefore, equipment is needed to communicate between the ATC (Air Traffic Controller) and the pilot. The problem reviewed in this final project is that coordination between Aviation Polytechnic of Indonesia Curug and Budiarto Air Traffic Services itself which has an impact on flight safety at Budiarto Airport. The purpose of this final project is to fulfill one of the graduation requirements to get an Associate Expert (AMD) degree in the Air Traffic Diploma 3 program at the Aviation Polytechnic of Surabaya and aim to provide insight as reference material for further researchers at the Surabaya Aviation Polytechnic and to find out the results of this research which is the problem of implementing ground-to-ground coordination for flight safety at Budiarto Airport. In this review, the samples are air traffic controller personnel who worked at the Budiarto aerodrome control tower unit and personnel of Aviation Polytechnic which is located at Budiarto Airport. The variable reviewed is variable (X), which is the coordination between Budiarto Air Traffic Services and the Aviation Polytechnic of Indonesia Curug. The data collection method that used is observation, quisioner, interviews and documentation. The data analysis method used is descriptive qualitative.